2013
DOI: 10.1007/s13197-013-1057-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing techniques on nutritional composition and antioxidant activity of fenugreek (Trigonella foenum-graecum) seed flour

Abstract: Fenugreek (Pusa Early Bunching) seeds were processed by using different processing methods viz. soaking, germination and roasting. Raw and processed fenugreek seed flours were analyzed for nutritional composition, anti-nutritional, and antioxidant activity. Raw fenugreek seed flour contained higher amount of dietary fiber (45.4 %) followed by 41.7 % in soaked seed flour, 40.9 % in roasted fenugreek seed flour and 31.3 % in germinated fenugreek seed flour. Processing of fenugreek seeds improved in vitro starch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 28 publications
5
80
2
1
Order By: Relevance
“…A similar trend was reported by Win et al (2011) for oven-roasted peanut extracts. Pandey and Awasthi (2015) also reported that roasting increased the total phenolic content in fenugreek seeds. The roasting process most likely increased the TPC through the following mechanisms: roasting might partially destroy the cell structure, resulting in the release of some bound phenolic compounds, which could then become more extractable in solvents (Zou et al, 2015).…”
Section: Resultsmentioning
confidence: 88%
“…A similar trend was reported by Win et al (2011) for oven-roasted peanut extracts. Pandey and Awasthi (2015) also reported that roasting increased the total phenolic content in fenugreek seeds. The roasting process most likely increased the TPC through the following mechanisms: roasting might partially destroy the cell structure, resulting in the release of some bound phenolic compounds, which could then become more extractable in solvents (Zou et al, 2015).…”
Section: Resultsmentioning
confidence: 88%
“…This treatment reduces the tannin content and increases IVPD (Mukuru ). In several studies, soaking of the legumes in distilled water was found to decrease polyphenol/tannin content and increase IVPD (Kataria and others ; Chau and Cheung ; Preet and Punia ; Rehman and Shah ; Abd El‐Hady and Habiba ; Shimelis and Rakshit ; Luo and Xie ; Pandey and Awasthi ). In contrast, for sorghum it was shown that only soaking in alkaline solution increases IVPD (Chavan and others ; Mukuru ; Vijayakumari and others ).…”
Section: Food Processing Methods For the Reduction Of Antinutritionalmentioning
confidence: 99%
“…Germination has been found to reduce polyphenol/tannin levels and improve the IVPD of several foods, including pearl millet (Pushparaj and Urooj ), sorghum (Elkhalil and others ), and legumes (Kataria and others ; Chau and Cheung ; Alonso and others ; Preet and Punia ; Ghavidel and Prakash ; Sangronis and Machado ; Shimelis and Rakshit ; Pandey and Awasthi ). In addition, autoclaving of germinated seeds have shown to be even more efficient for kidney beans (Shimelis and Rakshit ).…”
Section: Food Processing Methods For the Reduction Of Antinutritionalmentioning
confidence: 99%
“…Overcoming this limitation is a major challenge for food scientists. Approaches such as soaking, germination, and roasting have been evaluated to reduce bitterness (Ertaş & Bilgiçli, ; Pandey & Awasthi, ) and utilized in formulating value‐added baked (Metwal, Jyotsna, Jeyarani, & Venkateswara Rao, ; Roberts, Cui, Chang, Ng, & Graham, ) and extruded products (Wani & Kumar, ). These processes alter the chemical composition of seeds (Pandey & Awasthi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Approaches such as soaking, germination, and roasting have been evaluated to reduce bitterness (Ertaş & Bilgiçli, ; Pandey & Awasthi, ) and utilized in formulating value‐added baked (Metwal, Jyotsna, Jeyarani, & Venkateswara Rao, ; Roberts, Cui, Chang, Ng, & Graham, ) and extruded products (Wani & Kumar, ). These processes alter the chemical composition of seeds (Pandey & Awasthi, ). Germination of fenugreek seeds (Mansour & El‐Adawy, ) enhances the antioxidant activity which is attributed to an increased content of polyphenols (Cevallos‐Casals & Cisneros‐Zevallos, ; Khole et al, ) and decreased fat and dietary fiber and increased protein contents (Pandey & Awasthi, ).…”
Section: Introductionmentioning
confidence: 99%